Comparison of the costs of care during acute illness by two community children's nursing teams. Issue 12 (6th December 2012) - Callery, Peter; Kyle, Richard G; Weatherly, Helen; Banks, Michele; Ewing, Carol; Powell, Peter; Kirk, Susan
Abstract : Objective: To compare the costs associated with care by two community children's nursing teams (CCNT). Design: A case study incorporating questionnaire survey, analysis of routinely collected data and analysis of costs in the north-west England. Patients: Children with acute illness referred for CCNT care. Interventions: Two CCNT provided care for 273 children during acute illness in order to reduce the number and duration of hospital admissions. Main Outcome Measures: Costs of CCNT, other services and costs to families. Results: The objectives of both CCNT included shortening and avoiding hospitalisations. Most (45 (58%) in case A and 150 (77%) in case B) children were referred for infections. There were differences in the proportion of children who had been hospitalised (45 (57.7%) and 78 (40%)), the mean number of services used before referral to CCNT (1.6 and 2.2) and the staffing profile of the CCNT. There was a statistically significant difference in the overall mean cost to the NHS of CCNT care (£146 and £238, 95% CI for difference of means 7 to 184), associated with higher proportions of children having telephone-only contact (two (3%) and 46 (24%)) and children using almost twice as many other health services during care by one CCNT (means 0.27 and 0.51). Conclusions: Costs of CCNT care can vary widely when all health service use is taken into account. Differences in the way CCNT are integrated with the urgent care system, and the way in which CCNT care is organised, could contribute to variations in costs.